Sholat Dan Tilawah Sebagai Sarana Dalam Menurunkan Stress: Studi Fenomenologi - Ilham Kurniawan; Vina Aprila Utami (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study explores the role of prayer (sholat) and recitation of the Qur'an (tilawah Al-Qur'an) as means to reduce stress through a phenomenological approach. In-depth interviews revealed that both practices have significant calming effects. Prayer, with its rhythmic movements and supplications, helps lower stress hormones such as cortisol and cultivates inner peace. Recitation of the Qur'an, through its rhythm and intonation, reduces anxiety and enhances tranquility. The combined effect of these practices effectively reduces stress, strengthens social and spiritual support, and enhances mental well-being. The study supports the importance of consistency in prayer and Qur'anic recitation practices, as well as engagement in religious communities to support effective stress management.